VARIASI KELUASAN MAKNA INTERPERSONAL TEKS “LASKAR PELANGI” BERBAHASA INDONESIA, INGGRIS, DAN MELAYU - Hapsari, Apriliana; Tou, Asruddin Barori (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2015)
Penelitian ini bertujuan untuk mendeskripsikan variasi keluasan makna interpersonal pada teks “Laskar Pelangi” berbahasa Indonesia, Inggris, dan Melayu serta faktor-faktor yang mendorong terjadinya tingkat variasi keluasan makna tersebut. Penelitian ini merupakan penelitian deskriptif kualitatif dengan objek penelitian adalah variasi keluasan makna interpersonal yang terealisasi dalam sistem gramatika MOOD pada tiap klusa dari ketiga teks multitranslasi. Data dianalisis dengan teknik hubung banding dengan membandingkan masing-masing klausa dari ketiga teks tersebut. Hasil penelitian menunjukkan tingginya tingkat variasi keluasan makna interpersonal pada T1:T2, sebesar 23,89, dan rendahnya tingkat variasi tersebut pada T1:T3, sebesar 2,82. Tingginya tingkat variasi disebabkan penambahan klausa pada T2, pengaruh skrip cerita film, faktor tujuan, serta faktor pembaca T2. Rendahnya tingkat variasi disebabkan persamaan akar bahasa dan budaya antara T1 dan T3 serta faktor tujuan penerjemahan. _____________________________________________________________________________________________________________ THE INTERPERSONAL MEANING BREADTH VARIATIONS ON MULTILINGUAL TRANSLATION TEKS “LASKAR PELANGI” IN BAHASA INDONESIA, ENGLISH, AND MALAY Abstract This study is aimed to describe the interpersonal meaning breadth variations on multilingual translation teks “Laskar Pelangi” in bahasa Indonesia, English, and Malay also to explore the motivating factors that occur inside those variations. This study was a descriptive qualitative research study. The object was interpersonal meaning breadth variations that were showed by the MOOD grammatical system in the clauses of the multilingual translation texts. The data were analyzed by comparing the realization of functional elements of the MOOD grammatical system in each clause of the text. The results of this study show that variations in interpersonal meaning breadth of T1:T2 are high, 23.89 whereas the variations of T1:T3 are low, 2.82. For T1:T2, the variation in interpersonal meaning breadth is high, because of the addition of clauses in T2, the influence of movie script, the translation purpose, and the target text’s readers. Meanwhile, for T1:T3, the variation in interpersonal meaning breadth is low because of the non-existence of new clauses in T2, the same language root of Indonesian and Malay and the purpose of translation. Keywords: MOOD grammatical system, interpersonal menaing breadth variation